2008
DOI: 10.1080/15470140802473689
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of Differences among Meeting and Exhibition Planners in their Destination Selection Criteria

Abstract: Destination selection criteria for meetings, conventions, trade shows, and other events have been explored by a variety of researchers. Most research in this area, however, has not evaluated how planners of different events rate the destination selection variables. The current study identified three international associations for different types of event professionals and compared members' ratings of 13 destination selection criteria. Findings show that there are differences in the most important criteria used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 25 publications
5
35
0
12
Order By: Relevance
“…Hultsman's later study (2001) confirmed that layout was considered the second most important exhibit hall attribute after the rental fee. Indeed, the members of the International Association of Exhibitions and Events rate exhibit space as the most important criterion for an attractive event or exhibition venue (DiPietro et al, 2008). This makes spatial layout a good indicator of service providers' efforts towards their customers.…”
Section: Spatial Layoutmentioning
confidence: 99%
See 1 more Smart Citation
“…Hultsman's later study (2001) confirmed that layout was considered the second most important exhibit hall attribute after the rental fee. Indeed, the members of the International Association of Exhibitions and Events rate exhibit space as the most important criterion for an attractive event or exhibition venue (DiPietro et al, 2008). This makes spatial layout a good indicator of service providers' efforts towards their customers.…”
Section: Spatial Layoutmentioning
confidence: 99%
“…Hospitality servicescape research has mainly been conducted in the context of hotels (Heide et al, 2007), restaurants (Kim and Moon, 2009;Liu and Jang, 2009), bars (Lin, 2010), theaters (Stuart and Tax, 2004), festivals (Taylor and Shanka, 2002), casinos (Lam et al, 2011), or general leisure settings (Wakefield and Blodgett, 1994). The existing research on the servicescape related to the convention setting is more focused on areas such as the exhibition attributes which encourage repeat visits (Whitfield and Webber, 2010), safety and security concerns (Hilliard and Baloglu, 2008), the relationship between the design elements used and creating an emotional connection for event attendees (Nelson, 2009), site and venue selection criteria (DiPietro et al, 2008;Robinson and Callan, 2005), the perceived quality and competitiveness of convention center facilities by both event organizers and attendees in terms of their attributes and services (Breiter and Milman, 2006;Wu and Weber, 2005) or the successful factors of a convention (Hultsman, 2001). There is a paucity of studies investigating the role and impact of the servicescape on customers' cognitive, affective and behavioral responses in event settings.…”
Section: Introductionmentioning
confidence: 99%
“…A number of authors have provided some inputs into the understanding and practical research of competitiveness in tourism destinations (De Keyser and Vanhove, 1994;Evans, Fox and Johnson, 1995;Faulkner et al, 1999;Hassan, 2000;Ritchie and Crouch, 1993;Crouch and Ritchie, 1999;Crouch and Ritchie, 2000;Ritchie and Crouch, 2003;Dwyer et al, 2000Dwyer et al, , 2002Newton, 2004, 2005;Bonn et al, 2005;Cracolici and Nijkamp, 2008;Crouch, 2010;Miller et al, 2008;Dragićević et al, 2009). But, there seems to be no generally accepted definition of competitiveness and the means to measure it (Croes 2005;Papatheodorou andSong 2005, Gomezelj andMihalič, 2008).…”
Section: Theory On Tourism Destination Competi-tivenessmentioning
confidence: 99%
“…Numerous studies have investigated specific destination variables that influence the selection of a destination for holding business events and its competitiveness (Ching-Fu, 2006;Crouch and Ritchie, 1998;DiPietro et al, 2008;Oppermann, 1996;Baloglu and Love, 2001;Crouch and Louviere, 2004;Chacko and Fenich, 2000;Oppermann and Chon, 1997;Yoo and Chon;2008, Zhang et al, 2007Qu et al, 2000).…”
Section: Business Tourism Destinationmentioning
confidence: 99%
“…Developing travel destinations, on the other hand, are less competitive and therefore have been trying to entice event tourists through other offerings, such as leisure and nightlife entertainment, lower cost of travel and lower event admission fees, and other destination-specific tourism products (Crouch and Ritchie, 1998;Getz, 2007). Although these destination attributes have been widely acknowledged as travel incentives and play a central role in destination selection (Chacko and Fenich, 2000;Comas and Moscardo, 2005;DiPietro et al, 2008;Fenich, 2001;Oppermann and Chon, 1997), it is still unclear how these attributes are related to tourism destination development. This literature void is addressed in the current research in the context of the developing travel destination of Macao, China.…”
Section: Introductionmentioning
confidence: 99%